PEMANFAATAN LIMBAH CANGKANG KERANG HIJAU (PERNA VIRIDIS) SEBAGAI ALTERNATIF ABSORBER PADA DESTILASI AIR LAUT TENAGA SURYA TIPE KOLEKTOR PLAT SINUSOIDAL - Paridawati Paridawati; Taufiqur Rokhman; Abdillah Abbas Romdhoni; Hari Iswanto; Sukwati Dewi Asrika; Mario Apriliansyah; Suprianto Wibowo (Jurnal Ilmiah Teknik Mesin, 2023)
The efficiency of destilator absorber full of green mussel shells was 34,67% from the researchvolume of 5L seawater, 28% from the research volume of 3L seawater, 37% from the researchvolume of 2L. The efficiency of destilator absorber ½ of green mussel shells was 31% from theresearch volume of 5L seawater, 27,67% from the research volume of 3L seawater, 32,67% fromthe research volume of 2L. The efficiency of destilator absorber without of green mussel shellswas 17,33% from the research volume of 5L seawater, 14,67% from the research volume of 3Lseawater, 20,67% from the research volume of 2L. Also obtained the percentage of full absorberdestilation of green mussel shells 8,55% from research of 5L seawater volume, 12,12% from theresearch volume of 3L seawater, 26,03% from the research volume of 2L seawater. The percentageof ½ absorber destilation of green mussel shells 7,6% from research of 5L seawater volume, 11,5%from the research volume of 3L seawater, 22,98% from the research volume of 2L seawater. Thepercentage of without absorber destilation of green mussel shells 4,29% from research of 5Lseawater volume, 6,32% from the research volume of 3L seawater, 15,05% from the researchvolume of 2L seawater. And the most optimal result of destilation of seawater volume is 2Labsorber full green mussel shells which is 651 ml.